The kinematics of HH 34 from HST images with a nine-year time baseline - Raga, Alejandro C.; Lora, Verónica (The astrophysical journal, 2012)
We study archival HST [S II ] 6716+30 and Hα images of the HH 34 outflow, taken in 1998.71 and in 2007.83. The 9 yr time baseline and the high angular resolution of these observations allow us to carry out a detailed proper-motion study. We determine the proper motions of the substructure of the HH 34S bow shock (from the [S II ] and Hα frames) and of the aligned knots within 30” from the outflow source (only from the [S II ] frames). We find that the present-day motions of the knots along the HH 34 jet are approximately ballistic, and that these motions directly imply the formation of a major mass concentration in 900 yr, at a position similar to the one of the present-day HH 34S bow shock. In other words, we find that the knots along the HH 34 jet will merge to form a more massive structure, possibly resembling HH 34S.